FRONTIERS IN SEAFLOOR MAPPING AND VISUALIZATION - Mayer L.A. (My University, 2006)
Over the past few years there have been remarkable and concomitant advances in sonar technology, positioning capabilities, and computer processing power that have revolutionized the mapping, imaging and exploration of the seafloor. Future developments must involve all aspects of the “seafloor mapping system,” including, sonars, ancillary sensors (motion sensors, positioning systems, and sound speed sensors), platforms upon which they are mounted, and the products that are produced. Current trends in sonar development involve the use of innovative new transducer materials and the application of sophisticated processing techniques including focusing algorithms that dynamically compensate for the curvature of the wavefront in the nearfield and thus allow narrower beam widths (higher lateral resolution) at close ranges . Future developments will involve “hybrid”, phase-comparison/beam-forming sonars, the development of broad-band “chirp” multibeam sonars, and perhaps synthetic aperture multibeam sonars. The inability to monitor the fine-scale spatial and temporal variability of the sound speed structure of the water column is often a limiting factor in the production of accurate maps of the seafloor; improvements in this area will involve continuous monitoring devices as well as improved ocean models and perhaps tomography. Remotely Operated Vehicles (ROV’s) and particularly Autonomous Underwater Vehicles (AUV’s) will become more important as platforms for seafloor mapping systems. There will also be great changes in the products produced from seafloor mapping and the processing necessary to create them. New processing algorithms are being developed that take advantage of the density of multibeam sonar data and use statistically robust techniques to “clean” massive data sets very rapidly. A range of approaches are being explored to use multibeam sonar bathymetry and imagery to extract quantitative information about seafloor properties, including those relevant to fisheries habitat. The density of these data also enable the use of interactive 3-D visualization and exploration tools specifically designed to facilitate the interpretation and analysis of very large, complex, multi-component spatial data sets. If properly georeferenced and treated, these complex data sets can be presented in a natural and intuitive manner that allows the simple integration and fusion of multiple components without compromise to the quantitative aspects of the data and opens up new worlds of interactive exploration to a multitude of users.
Keywords: MULTIBEAM SONAR; OCEAN MAPPING; FUTURE DEVELOPMENTS; SEAFLOOR CHARACTERIZATION; INTERACTIVE 3D VISUALIZATION